« Pas de retour à nos maisons sans satisfaction de nos revendications ». Le Hirak du Rif en actes face au Makhzen - Ahmed Chapi (L’Année du Maghreb)
In Morocco, while the protests led by the Hirak Rif Movement (2016-2017) were eventually stifled due to the scale of the repressive campaign, the various attempts to stop the movement have first helped to fuel the protest dynamic. Our main argument is that while the movement's activists employed initially (and above all) the most routine tactics of protest (such as demonstrations whose times and locations were publicly announced in advance), they progressively innovated tactically (through, for example, surprise demonstrations known as "chen-ten" and pot-banging protests), moved to new protest sites (such as the various districts of Al Hoceima and the beaches) and encouraged the involvement of heterogeneous protest profiles (many of whom are young and/or have a distant connection to the activist universe) ; these processes fostered the movement's continuity and gave it a disruptive character. The mobilization relied on informal networks of proximity, everyday forms of solidarity and devices of group representation such as the oath (al-qasam). Protesters felt mutually obliged to continue protesting despite the risks, making it difficult to "step back". Our article focuses on the activists in the city of Al Hoceima, which was the epicenter of the protests. It draws on various sources (semi-structured interviews, observations, video corpus, digital traces, and electronic press) collected as part of an ongoing doctoral dissertation. The interviews were conducted in Al Hoceima, in various European cities where some of the activists have taken refuge, and online. To provide empirical evidence, we have selected several protest sequences that appeared to us as bifurcation moments. First, we look back at the conditions of emergence of a movement that resolutely rejects the presence of any kind of organization, be it partisan, union-related, or associative. During the first few months (October 2016-February 2017), protest tactics are rather routine (sit-ins and marches whose times and locations are publicly announced in advance, strikes). However, as security forces start blocking access to the main public squares, we'll see in the second part that, from the end of February 2017, activists develop "surprise demonstrations" in order to circumvent these police restrictions and take to the streets once again. This new form of protest fosters broad popular participation and instills a new protest momentum, as activists are questioned daily by inhabitants about the date of the next demonstration, in turn, prompting them to take to the streets frequently. Thirdly, we'll see that attempts by the wali and local elected representatives to bypass and delegitimize the movement have the opposite effect: these attempts contribute to the spatial diffusion of contention, as activists organize gatherings in all parts of the city over several days, generating collective emulation and making the Hirak an everyday reality. Finally, in May 2017, when the decision of mass arrests is made, these target the leaders. However, the protests continue in the following weeks, through night-time rallies in the neighborhoods, pot-banging and marches (some of which on the beaches), thanks to activists embedded in the movement's mobilization networks who have not (yet) been detained. These activists remain committed despite the heightened risks, as they gradually develop or strengthen a strong inclination to protest, taking part in various actions throughout the protest sequence (such as surprise demonstrations and neighborhood rallies). The looser, more horizontal division of activist labor at work in the Hirak, in comparison with traditional activist organizations, favors the reconfiguration of the movement in terms of protest tactics, locations and profiles, enabling it to sustain itself over time.